2016
DOI: 10.1080/01431161.2016.1204027
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the status of submerged aquatic vegetation using novel optical parameters

Abstract: The reservoirs constructed throughout Brazil for electrical power generation following its industrial and socioeconomic development now favour abundant aquatic macrophyte growth. Nova Avanhandava Reservoir is fully inhabited by submerged aquatic vegetation (SAV) that poses serious ecological and economic threats. The overall goal of this study was to assess the radiation availability in the water column in the Nova Avanhandava Reservoir and analyse its influence on SAV development and growth. In addition to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Upstream areas are relatively shallow compared to the downstream areas, which could cause resuspension of bottom sediments induced by strong winds and water flow [1,48]. In downstream areas, the slow water flow due to the proximity of the dam and higher depths favored the deposition of suspended solids on the bottom, which resulted in a lower K d(PAR) , as shown by Rotta et al [15]. The region with a high K d(PAR) was observed near Figure 4a, and is probably caused by the presence of a sand mining company, indicated by the black arrow in Figure 4.…”
Section: Kd(par) Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Upstream areas are relatively shallow compared to the downstream areas, which could cause resuspension of bottom sediments induced by strong winds and water flow [1,48]. In downstream areas, the slow water flow due to the proximity of the dam and higher depths favored the deposition of suspended solids on the bottom, which resulted in a lower K d(PAR) , as shown by Rotta et al [15]. The region with a high K d(PAR) was observed near Figure 4a, and is probably caused by the presence of a sand mining company, indicated by the black arrow in Figure 4.…”
Section: Kd(par) Mappingmentioning
confidence: 99%
“…The region with a high K d(PAR) was observed near Figure 4a, and is probably caused by the presence of a sand mining company, indicated by the black arrow in Figure 4. Sand dredging leads to sediment resuspension that increased the K d values at nearby locations [15]. Based on the K d(PAR) map, it can be stated that most of these particles resuspended from the bottom were deposited again at locations approximately 2 km beyond the extraction point.…”
Section: Kd(par) Mappingmentioning
confidence: 99%
“…Rotta et al (2012) mapped SAV in the Porto Colômbia Reservoir (Uberaba River, Minas Gerais State) using an echosounder detecting presence of SAV up to 7 m depth. The densest SAV was observed by Batista et al (2012) at depths between 2 and 4 m in Taquaruçu reservoir (Paranapanema River, between Paraná and São Paulo State), showing SAV growing even at the depth range of 6-8 m. The status of SAV in Nova Avanhandava Reservoir (Tietê River, São Paulo State) was analyzed by Rotta et al (2016) who reported their occurrence at depths up to 9 m. The detection of bottom signal is difficult at such deeper waters even when using in situ sensing due to the attenuation and scattering of radiation in the water column. Rotta et al (2016) concluded that it is necessary to recalibrate and tune existing radiative transfer models with lots of field data in order to achieve the desired accuracy in mapping SAV biomass and height using satellite data.…”
Section: Introductionmentioning
confidence: 95%
“…Several other studies have concluded that high resolution airborne or satellite images may not be able to extract information about SAV in relatively deep reservoirs using frequently adopted simple methods such as image classification or empirical band ratios because of the target's low signal to noise ratio (Rotta et al, 2016(Rotta et al, , 2013Boschi, 2011;Malthus, 2017). Semi-analytical models have been proposed as an alternative to remove the water column influence and to retrieve bottom reflectance in water bodies to study submerged targets.…”
Section: Introductionmentioning
confidence: 99%
“…Infusion of nutrients (nitrogen (N) and phosphorus (P)) from the land via runoff often leads to eutrophication increasing the primary production of phytoplankton and macrophytes [3]. In oligo-to-mesotrophic reservoirs, the submersed species of macrophytes, which are usually rooted, occupy the edges and often the slow-moving zones of rivers [4]. They are dependent on the sediment supply and light availability for their optimal growth [5].…”
Section: Introductionmentioning
confidence: 99%